2005
DOI: 10.1108/02652320510612483
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting the non‐adopter category in the diffusion of internet banking

Abstract: PurposeFor a new technology‐based product or service at an early stage of diffusion, it is likely that only a small subset of consumers have adopted it. When non‐adopters still comprise the majority of the target populations, describing all non‐adopters as a homogeneous population may be inaccurate and inappropriate. It is important to be able to identify differences, not only between adopters and non‐adopters, but also among non‐adopters, the latter providing a means of identifying the consumer segments likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
118
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(136 citation statements)
references
References 69 publications
(94 reference statements)
13
118
0
5
Order By: Relevance
“…Consistent with prior studies (e.g., Baraghani, 2007;Chen & Barnes, 2007;Chong, Oii, Lin, & Tan, 2010;Dauda et al, 2007;Gefen, 2000;Lee et al, 2005;McKnight & Chervany, 2002), the findings in this study show that trust will influence the adoption of online banking in Selangor, Malaysia. Chong et al (2010) stated that people from developing countries tend to be more cautious when using online banking services as it involves money and people are used to conduct monetary transaction in-person.…”
Section: Trustsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with prior studies (e.g., Baraghani, 2007;Chen & Barnes, 2007;Chong, Oii, Lin, & Tan, 2010;Dauda et al, 2007;Gefen, 2000;Lee et al, 2005;McKnight & Chervany, 2002), the findings in this study show that trust will influence the adoption of online banking in Selangor, Malaysia. Chong et al (2010) stated that people from developing countries tend to be more cautious when using online banking services as it involves money and people are used to conduct monetary transaction in-person.…”
Section: Trustsupporting
confidence: 81%
“…As online banking services are delivered through internet, Lee, Kwon and Schumann (2005) suggested that customers have to be familiar with the technologies, such as personal computer and web browser. This was supported by the study conducted by Laforet and Li (2005) who investigated the customers' attitude towards the online banking services in China.…”
Section: Customers' Experiencementioning
confidence: 99%
“…Meanwhile a study by Wan, Luk, & Chow (2005) cites that even though internet banking adoption is most affected by convenience, but it cannot compete with ATM because ATM is the only channel that enable withdrawal of cash at anytime and does not require customer to have an access to computer facilities. In addition, Lee, Kwon, & Schumann (2005) also found convenience as key factor on determining users' intention in adopting internet banking services. At the same time, another study by Abdul Kabeer Kazi (2013), the studies in Pakistan shows that a higher education level of students has more intention in adopting internet banking because of convenience.…”
Section: Conveniencementioning
confidence: 99%
“…Consumers should have a familiarity with computers and must have skills on using web browsers because internet act as a key medium for internet banking services (Lee, Kwon, & Schumann, 2005). Consumers that have more knowledge on computer technologies may easily adopt internet banking and enhance their efficiency in the use of internet banking.…”
Section: Knowledge and Self-efficacymentioning
confidence: 99%
“…Based on a survey of 1355 respondents [37], it was discovered that current and prospective adopters perceived convenience as a determinant of intention to adopt e-services. Convenience in e-learning refers to the capability to access e-courses at anytime and anywhere.…”
Section: Perceived Conveniencementioning
confidence: 99%